P98 Improving diagnosis and management of COPD: learning from a programme of national improvement projects. (2nd December 2011) - Blackaby, C; Lord, Z; Thompson, C; Porter, A; Duncan, P; Okosi, O; Wall, H
Abstract : Introduction: Chronic Obstructive Pulmonary Disease (COPD) represents an increasing burden for the NHS. National data indicate significant variation in the quality and consistency of diagnosis and management of COPD, with low recorded prevalence and increasing admissions. Early, accurate diagnosis and proactive management can modify disease progression to improve quality of life and use of health care resources. This national improvement programme aims to reduce variation and optimise diagnosis, treatment and use of healthcare resources through implementation of chronic disease management approaches. Methods: 16 project sites from primary and secondary care adopted a systematic approach using improvement methodology to analyse existing patient pathways for COPD diagnosis and management, test changes and evaluate impact. Primary care and acute admission data, process mapping and patient feedback was analysed to identify risk, duplication and omissions in care and to evaluate the impact of changes implemented. Results: Great inaccuracy was identified in practice registers for COPD and asthma. Projects demonstrated that up to 69% of COPD patients also had a recorded diagnosis of asthma; up to 15% had no spirometry recorded and up to 40% had incomplete results. 21–43% of patients had an FEV1 /FVC ratio >0.7, which is not indicative of COPD. Systematic process improvement of inpatient and community pathways in one project delivered savings of £170k while medicines management reduced one practice's respiratory prescribing costs by £1.5k per month. Consistent coding and use of self management support increased early identification of exacerbation and reduced the rate of COPD exacerbations resulting in admission from 8% to 5% in another project. Conclusion: Systematic improvement approaches can help reduce variation, improve quality, reduce admissions, and contain costs without significant impact on resources. Detailed practice-level information can demonstrate significant scope to improve the quality of diagnosis and reliability of appropriate treatment. Consistent coding in primary care is essential for proactive management of patients. Accurate diagnosis and regular review to optimise medicines use can deliver overall cost reductions. Further work is needed to demonstrate how teams can best use existing resources to deliver proactive management of COPD.